Respuesta :

Answer:

[tex]y(x) = e^{-x} +C[/tex]

Step-by-step explanation:

As per the question,

Given first-order differential equation is

 y' = -y

That is,

[tex]\frac{dy}{dx} + y = 0[/tex]

[tex]\frac{dy}{y} = -dx[/tex]

On Integrating both side,

[tex]\int \frac{dy}{y} = \int -dx[/tex]

As we know that,

[tex]\int \frac{1}{x} dx = ln\ x +C[/tex]

Therefore,

[tex]\int \frac{dy}{y} = \int -dx[/tex]

[tex]ln\ y = e^{-x} + C[/tex]

Hence the required function is

[tex]y(x) = e^{-x} +C[/tex]

ACCESS MORE